Effects of Aerobic Exercise on Physical Condition in Chronic Kidney Disease Patients: Scoping Review - Iftinan Nida Firdaus; Meira Erawati; Wahyu Hidayati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Chronic kidney disease (CKD) can cause changes in physical condition and cause cardiovascular problems to death. The development of CKD can be prevented by doing physical activity, one of which is aerobic exercise. Studies related to the effects of aerobic exercise on physical condition, especially in patients with chronic kidney disease, are still limited, so further studies are needed. The purpose of this study was to determine the effect of aerobic exercise on physical condition in patients with chronic kidney disease. The method used is a scoping review based on the PRISMA flow diagram. Article searches were conducted using electronic databases or internet searches, some databases used as article selection are ScienceDirect, Pubmed, and Springerlink. In conducting the search using the keywords